Dilemmas of Discrimination Against People with Disabilities in the Health Care System - Ingrida Baranauskienė (Social Welfare: Interdisciplinary Approach, 2023)
In recent decades, there has been a debate in health care practice for people with disabilities that there is already a shift from a medical model to a social model, and new models are developed, such as the human rights model, which can be linked to the United Nations Convention on the Rights of Persons with Disabilities. On the other hand, in many countries, including Lithuania, the analysis of the situation of people with disabilities in the health care system in terms of discrimination is not carried out systematically, and it can hardly be said that this topic is a priority. The scientific study has revealed that this is the case. In this context, the questions naturally arose: what is the situation of people with disabilities in the health care system in Lithuania? Are they discriminated against? If discrimination against people with disabilities persists, what is its manifestation? These and other similar questions reflect the scientific problem of the article. Answering these questions requires obtaining the data of the research, needs, and challenges of people with disabilities, their relatives, and professionals assisting people with disabilities in the Lithuanian health care system were analyzed, which were processed referring to the principles of thematic analysis. The findings of the research prove the multidimensional expression of discrimination against people with disabilities in Lithuania’s healthcare system.